Optimised preliminary design of a kayak-ergometer using a sliding footrest-seat complex - Begon, M.; Colloud, F. (The Engineering of sport 7, Volume 2, 2008)
In sport sciences, ergometers are frequently used to provide a sheltered experimental environment. In situ, the measurement difficulties ranged from to the 3D kinematics to the contact forces. However, an ergometer has to reproduce the dynamics of the in situ movement for an accurate mechanical analysis. During a kayaking task, an ergometer with a sliding footrest-seat complex (trolley) reproduces better the acceleration of the Kayak-Athlete-Paddle system over the whole kayaking cycle. The purpose of this study was to improve the design of this ergometer using optimization of the mechanism of the footrest-seat complex translation. The whole body kinematics and the paddle tip forces were recorded for twelve flatwater athletes. Firstly, the acceleration of the Athlete-Paddle System was estimated using the propulsive force and a drag model Secondly, the Ergometer-Athlete-Paddle model was developed within HuManS toolbox to perform simulations, These simulations were driven by the kinematics tasks of the athlete. The Output of the Simulation was the antero-posterior absolute acceleration. The elastic cord linking the frame to the sliding complex was modelled as a polynomial function of order 3: F=a3x³+a2X²+a1x, with x the Position of the trolley on the frame. The parameters of this model were optimised by matching the accelerations of the Athlete-Paddle system over a whole cycle of the two cases. The fitness function was defined as the root mean square difference between the two cases and was minimized using an evolutionary algorithm. The optimization was carried out with two elastic cord models: a simple spring (a3=a2=0) and the full model which fits well a bungee.